ANALISIS KINERJA LINUX PADA MINI PC: KINERJA PROSESOR, MEMORI DAN DISK DRIVE - Fryonanda, Harfebi; Andre Febrian Kasmar; Muhammad Ibrahim Nasution; Edwar Rosman; Wirda Nissa (ABEC Indonesia, 2023)
This study aims to analyze mini PC performance in various aspects, including CPU, disk, memory, graphics, and operating system (OS) functions. The research was conducted by testing the mini PC using several testing methods, which involved compiling the Linux kernel, testing disk performance using SQLite, measuring memory performance using Intel Memory Latency Checker, testing graphics performance with Xonotic, and testing OS functions with Glibc Benchmarks. The results of this study provide an overview of mini PC performance in these various aspects but also indicate the need for additional testing and further analysis to understand mini PC performance more comprehensively.